Analyzing Factors Affecting the Use of Digital Technology to Improve the Quality of Life of Older Adults - Thanakijborisut, Yuthapoom (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2024)
Thailand’s rapid transformation into a digital society presents significant challenges for older adults as they must adapt to swiftly evolving technologies. This study aims to analyze the factors affecting the use of digital technology to improve the quality of life of older adults in line with contemporary societal demands. Data were collected from 450 older adults aged 60 and above in Bangkok through questionnaires and interviews. Logistic regression analysis was used to estimate the impact of various factors on the probability of older adults improving their quality of life using digital technology. The results indicate that increased age and being currently married are significantly associated with a lower probability of older adults improving their quality of life through digital technology. Conversely, an increase in household members, possession of a bachelor’s degree or higher, and prior experience with technology significantly contribute to the likelihood of older adults using digital technology to improve their quality of life. Specifically, these factors increase the probability of older adults improving their quality of life by an average of 3.29%, 24.91%, and 30.24%, respectively, with statistical significance. Therefore, the use of digital technology plays a crucial role in the daily lives of older adults, enabling them to enhance their quality of life and reduce their dependency on their families.